State Authorities and Legal Informational Marketing in Conditions of Transition to Democratic: The Social and Cultural Aspects - Mordovtsev, Andrey Yu.; Mamychev, Alexey Yu.; Mordovtseva, Tatyana V.; Mirzorin, Mikhail L. (International Review of Management and Marketing, 2016)
The article reveals the original aspects of formation of legal marketing information in the transition (transitive) public-political field. The paper studied the nature of the legal information in a broad sociocultural space, revealed its peculiarities and social importance in the modern world. For a more cost-effective transition of legal information it is necessary to conduct mass marketing of government authorities and the relevant legislation in the environment of a democratic society. In general, provisions defined herein largely explain the features of a democratic state creation in the former Soviet political and legal environment, as well as why the period of large-scale socio-political and socio-economic transformation in Russia is not yet complete. Keywords: legal information, state authority, legal system, sociocultural experience, civil society, legitimacy, marketing, marketing transition JEL Classifications: H10, K40, K49